The Aestheticization of Saung: Sundanese Vernacular Space in Contemporary Traditional Restaurants, Bandung - Edwin Widia; Sunarmi Sunarmi; Siti Badriyah (Journal of Social Research, 2025)
This paper explores the aestheticization of the Saung, a traditional Sundanese hut, as a vernacular cultural object that has undergone transformation in the contemporary urban context of Bandung, Indonesia. Originally a functional agrarian dwelling, the Saung has been recontextualized in restaurants and public cultural events, where its meaning oscillates between tradition and modernity, symbolism and function. Drawing on phenomenology and Bourdieu’s practice theory, particularly cultural capital and symbolic negotiation, this study employs field observations and in-depth interviews to reveal lived experiences of waas (nostalgic memory), nineung (longing), and nyawang (contemplative gaze), which collectively shape the aesthetics of rarasaan. These affective and sensory dimensions position the Saung not only as architecture but also as an inter-collective space that mediates cultural identity, memory, and imagination. By situating the Saung within the Traditional–Modern and Symbolic–Functional quadrants, this paper demonstrates how processes of restructuring, reconstruction, deconstruction, and replication function as adaptive design strategies. The findings highlight the Saung as a site of cultural oscillation and a resilient vernacular form, offering insights into how vernacular settlements can endure and transform under conditions of globalization.